Prevalence and Determinants of Soil-Transmitted Helminthic Infections among School Children at Goro Primary School, South West Shewa, Ethiopia - Tigist Tiruneh; Geleta Geshere; Tsige Ketema (International Journal of Pediatrics)
Background. Soil-transmitted helminths (STH)/geohelminths are human parasitic nematodes which need soil contact for their egg development and become infectious. It is widely prevalent in developing countries. In Ethiopia, too, the same problem exists although the prevalence varies from place to place depending on the presence of risk factors and hygienic status of the community. Therefore, the current study is designed to assess the prevalence and determinants of STH among school children at Goro Primary School of Southwest Ethiopia. Methods. A cross-sectional study design was employed from April to June 2019. The stool samples were collected in prelabeled, clean, and leak-proof stool cups and examined immediately. Direct wet mount and formalin ether concentration techniques were utilized to detect the STHs in a stool sample collected from all study subjects. A total of 387 stool samples were analyzed. Moreover, community- and individual-level risk factors associated with STH infection were assessed using semistructured questionnaire. Results. The overall prevalence of soil-transmitted helminth infections observed at the study area was 15.8% (n=61/387). Among these, the most abundant STH parasite was hookworms (n=39/61, 63.93%) followed by Ascaris lumbricoides (n=22/61, 36.06%). Factors independently associated with soil-transmitted helminth infections were children from illiterate mother (AOR=2.3, 95% CI: 1.1-4.8, P=0.021), lack of habit of wearing shoes (AOR=4.1, 95% CI: 2.0-8.5, P<0.001), lack of frequent handwashing practice before meal (AOR=2.3, 95% CI: 1.2-4.5, P=0.019), use of unprotected drinking water (AOR=39, CI:3.9-393, P=0.002), and presence of dirt in their fingernails (AOR=3.5, 95% CI: 1.8-6.9, P<0.001). Conclusions. STH infection observed in the study area could be classified into the low-risk area group (according to the World Health Organization classification) calling for none or case-by-case treatment. Thus, enhancing awareness of the community in the study area on how to keep personal hygiene and environmental sanitation is quite important to keep the burden to a controllable level, besides implementation of regular deworming program in the locality.